Relative Sensitivity of Depth Discrimination for Ankle Inversion and Plantar Flexion Movements. Issue 1 (February 2014) - Black, Georgia; Waddington, Gordon; Adams, Roger
25 participants (20 women, 5 men) were tested for sensitivity in discrimination between sets of six movements centered on 8°, 11°, and 14°, and separated by 0.3°. Both inversion and plantar flexion movements were tested. Discrimination of the extent of inversion movement was observed to decline linearly with increasing depth; however, for plantar flexion, the discrimination function for movement extent was found to be non-linear. The relatively better discrimination of plantar flexion movements than inversion movements at around 11° from horizontal is interpreted as an effect arising from differential amounts of practice through use, because this position is associated with the plantar flexion movement made in normal walking. The fact that plantar flexion movements are discriminated better than inversion at one region but not others argues against accounts of superior proprioceptive sensitivity for plantar flexion compared to inversion that are based on general properties of plantar flexion such as the number of muscle fibres on stretch.